A set of constitutive functions for dried body to predict entire deformation process of ceramic products during firing. Issue 8 (6th November 2017) - Matsubara, Seishiro; Tarada, Kenjiro; Kobayashi, Takaya; Saitou, Toshiyuki; Umeda, Manabu; Mihara, Yasuko; Oide, Kai; Shin, Hiroto; Katsuda, Yasuhiro
Abstract : Purpose: The purpose of this paper is to propose a set of constitutive functions for dried bodies for accurate prediction of the entire deformation process of ceramic products during firing and to present relevant methods for determining their coefficients from a series of respective thermo-mechanical analysis (TMA) tests. Design/methodology/approach: The function forms of the sintering-induced strain rate, viscoplastic multiplier and elastic modulus are formulated in order with reference to empirical data of relative densities. Separate TMA tests are conducted to identify their coefficients, while a stairway thermal cycle test is carried out to identify the parameters in the densification rate. Then, various finite element analyses (FEA) are performed for accuracy confirmation. Findings: The performances of the present constitutive functions along with the identified material parameters were validated in comparison with the relevant test results. It has then been confirmed that these functions enable us to some extent to accurately estimate the non-mechanical and mechanical deformations of dried bodies during firing. Also, by performing FEA of an actual sanitary ware product, the applicability and capability of the proposed set of constitutive functions could be demonstrated. Practical implications: The present methodology with the proposed constitutive functions is a simple, but reliable and practical approach for simulating the deformation process of arbitrary ceramic products subjected to firing and applicable for practical applications in various engineering fields. Originality/value: The constitutive functions of the viscoplastic multiplier and elastic modulus, which enable us to properly characterize the mechanical behavior of dried bodies subjected to firing, are originally formulated in analogy with that of the sintering-induced strain.